Disruption of each of the secreted aspartyl proteinase genes SAP1, SAP2, and SAP3 of Candida albicans attenuates virulence. - Hube, B (1997)
Secreted aspartyl proteinases (Saps), encoded by a gene family with at least nine members (SAP1 to SAP9), are one of the most discussed virulence factors produced by the human pathogen Candida albicans. In order to study the role of each Sap isoenzyme in pathogenicity, we have constructed strains which harbor mutations at selected SAP genes. SAP1, SAP2, and SAP3, which are regulated differentially in vitro, were mutated by targeted gene disruption. The growth rates of all homozygous null mutants were similar to those of the isogenic wild-type parental strain (SC5314) in complex and defined media. In medium with protein as the sole source of nitrogen, sap1 and sap3 mutants grew with reduced growth rates but reached optical densities similar to those measured for SC5314. In contrast, sap2 null mutants tended to clump, grew poorly in this medium, and produced the lowest proteolytic activity. Addition of ammonium ions reversed such growth defects. These results support the view that Sap2 is the dominant isoenzyme. When sap1, sap2, and sap3 mutants were injected intravenously in guinea pigs and mice, the animals had increased survival rates compared to those of control animals infected with SC5314. However, reduction of proteolytic activity in vitro did not correlate directly with the extent of attenuation of virulence observed for all Sap-deficient mutants. These data suggest that SAP1, SAP2, and SAP3 all contribute to the overall virulence of C. albicans and presumably all play important roles during disseminated infections.